Oxidation kinetics of organic disintegration products of yeast in cavitation conditions - Бернацкая, Наталия Любомыривна; Старчевский, Владимир Людвигович (Eastern-European Journal of Enterprise Technologies, 2014)
The oxidation features of yeast cells in the glucose solution under acoustic cavitation in order to determine the influence patterns of acoustic cavitation on the rate of water purification from biological contamination was investigated in the paper. It was shown that the disintegration rate of the microorganisms under the influence of ultrasound is described by the first-order equation, whereas the change in COD of dispersion of yeast in time under acoustic cavitation is described by the second-order kinetic equation. Oxidation of organic compounds of yeast cells in acoustic cavitation conditions proceeds by a radical chain mechanism. This is confirmed by the dependence of the rate constant on the concentration of oxygen, dissolved in a given system. The glucose oxidation rate under acoustic cavitation is much lower than the yeast oxidation rate in an aqueous dispersion. Increasing the glucose concentration in the dispersion of the yeast leads to slowing down the process at a constant concentration of yeast cells in the system. It was shown that glucose inhibits the oxidation of organic substances, contained in yeast cells. The obtained results allow to optimize the treatment process of wastewater of the food enterprises.